2010
DOI: 10.1089/tmj.2009.0076
|View full text |Cite
|
Sign up to set email alerts
|

E-health in China: Challenges, Initial Directions, and Experience

Abstract: China started to pay more attention to the construction of a regional and national health information network after the outbreak of the severe acute respiratory syndrome (SARS) epidemic in 2003. The construction of a public health system is considered the most important part of national medical reform, with information and computer technology serving as the key to deploying regional collaborative medical service, also known as e-health. In this paper, we analyze the difficulties in carrying out e-health projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 7 publications
1
26
0
Order By: Relevance
“…C2: Technology and Interoperability -Challenges surrounding integration/interoperability [19], [20], [21], [22], [23], [24] and standardisation of technologies/lack of data standards [9], [25], [26] were two barriers that appeared often in the analysed set of literature. Interoperability should allow for the unified integration of varied technologies to enable secure and fast access to health data and to patient information situated in different locations.…”
Section: Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…C2: Technology and Interoperability -Challenges surrounding integration/interoperability [19], [20], [21], [22], [23], [24] and standardisation of technologies/lack of data standards [9], [25], [26] were two barriers that appeared often in the analysed set of literature. Interoperability should allow for the unified integration of varied technologies to enable secure and fast access to health data and to patient information situated in different locations.…”
Section: Challengesmentioning
confidence: 99%
“…Interoperability should allow for the unified integration of varied technologies to enable secure and fast access to health data and to patient information situated in different locations. However, the barriers identified also suggest a need for the standardisation of system components and services so that healthcare providers can avoid issues such as lack of data standards permitting the exchange of clinical data [26]. One such recent technology that can be used to overcome such hurdles is FHIR (Fast Healthcare Interoperability Resources).…”
Section: Challengesmentioning
confidence: 99%
“…Post SARS, People's Republic of China also has begun to employ e-health more systematically. 48,49 Scanning the literature reveals that many other developing countries in the region use telehealth to varying degrees, for various purposes, and with varying success, but mostly in the context of projects; there is little evidence of sustained application of programs and poor publication for any single country or the region as a whole.…”
Section: Telehealth In Asiamentioning
confidence: 99%
“…In many other parts of the world, attention has also been devoted to the construction of e-health infrastructures using information and computer technology. China, for example, had supported some demonstration projects that enabled the setup of an economical, practical, reliable system so that medical records and laboratory results could be reviewed anywhere (Zhao et al, 2010). A multi-clinic randomized controlled trial in Malaysia reported that a text messaging reminder system was effective in improving attendance rate in primary care (Leong et al, 2006).…”
Section: Telehealthmentioning
confidence: 99%